Antimicrobial Activity of Morinda citrifolia L. - Noviana, Rena; Fajrina, Anzharni; Eriadi, Aried; Asra, Ridho (Asian Journal of Pharmaceutical Research and Development, 2021)
Objectives: The aim of this research was to provide knowledge that Morinda citrifolia L.was not only fruit and the leaves can be used as an antimicrobial. Parts of Morinda citrifolia L.(Noni) such as seeds were proven to be able to inhibit microbial growth. Antimicrobial was substances that inhibit growth or kill other microorganisms such as bacteria, viruses, fungi, protozoa and rickets. Data Sources Study Selection: The main references used in this review article through trusted sites such as Pubmed, Pubcem, Science Direct, NCBI, Research Gate, Google Scholar, and other published and trustworthy journals. Conclusion: Noni plant (Morinda citrifolia L.) was a medicinal plant that has antimicrobial properties because it contained secondary metabolites of flavonoid and phenol. The fruit and leaves were part of noni plant which has the highest potential for antimicrobial activity. The use of antimicrobial is one way of dealing with infectious diseases. So, the noni plant could be developed as an alternative of herbal product in overcoming the problem of antibiotic resistance.